2022
DOI: 10.1021/acscatal.2c04794
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Carbon Interior-Modified Mesoporous Silica-Confined Nickel Nanoclusters for Stereoselective Hydrogenation

Abstract: Hydrodearomatization attracts extensive interest for removing polycyclic aromatic hydrocarbons in diesel but still suffers from sluggish efficiency due to the vulnerable sulfur resistance of noble metal catalysts and inferior hydrogenation performance of traditional transition-metal catalysts. Herein, we propose a low-temperature in situ carbonization of the template strategy for constructing N-doped carbon interior-modified MCM-41 (NC@MCM)-confined ultra-dispersed Ni nanocluster catalysts (Ni/NC@MCM). The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…The C atoms adjacent to pyridine- N tend to react with –OH to form pyridone- N , which becomes an ORR catalytic active site . The higher content of pyridinic- N and Pd(0) in Pd/MR1-SA-CaCO 3 indicates more active sites for ORR catalysis, , which means Pd/MR1-SA-CaCO 3 should outperform rest two samples in terms of the ORR performance.…”
Section: Resultsmentioning
confidence: 99%
“…The C atoms adjacent to pyridine- N tend to react with –OH to form pyridone- N , which becomes an ORR catalytic active site . The higher content of pyridinic- N and Pd(0) in Pd/MR1-SA-CaCO 3 indicates more active sites for ORR catalysis, , which means Pd/MR1-SA-CaCO 3 should outperform rest two samples in terms of the ORR performance.…”
Section: Resultsmentioning
confidence: 99%
“…After the introduction of Ni, a small part of the micropores in the samples collapse into the mesopores at high temperatures. The OH-containing alkanol solvents can easily induce the formation of an organic matrix around the Ni precursor, thereby blocking the micropores of YP80 and resulting in the formation of more mesoporous structures, which indicates that the Ni is confined to the micropores of YP80. , …”
Section: Resultsmentioning
confidence: 99%
“…The OH-containing alkanol solvents can easily induce the formation of an organic matrix around the Ni precursor, thereby blocking the micropores of YP80 and resulting in the formation of more mesoporous structures, which indicates that the Ni is confined to the micropores of YP80. 17,26 The corresponding pore size distribution (a) and N 2 adsorption isotherms (b) of the catalysts are displayed in Figure 1. All the samples had a similar pore size distribution, and the pore size of the samples was around 0−2 nm.…”
Section: Catalytic Hydrogenation Testmentioning
confidence: 99%
“…Recently, Shu et al reported the loading of nickel clusters on the surface of mesoporous MCM-41 materials, demonstrating favorable catalytic effects [ 48 ]. They initially calcined mesoporous silica containing the CTAB template at 300 °C to obtain mesoporous silica with carbon/nitrogen hybridization.…”
Section: Applications Of Mesoporous Silicamentioning
confidence: 99%